Pengaruh Parkir Badan Jalan Terhadap Kinerja Ruas Jalan Bandang – Jalan Veteran Utara Makassar - Dimas, Dimas; Mallawangeng, Tamrin; Yunianti, Nur Hadijah (Program Studi Teknik Sipil Universitas Bosowa, 2025)
Traffic problems that arise due to the activity of vehicles parked on the Bandang - North Veteran Road Agency are certainly detrimental to road users, such as when the vehicle is parked or when the vehicle leaves the park. Therefore, the aim of this research is to determine the effect of parking activities on traffic performance and road service levels around Jalan Bandang - Jalan Veteran Utara Makassar. The type of method used is a descriptive research method, where data collection is obtained from geometric surveys of roads, traffic volume, vehicle speed and parking accumulation. The results of the research show that the influence of on-street parking has on traffic performance on the Jalan Bandang - Jalan Veteran Utara section, based on the analysis results Monday, Thursday, Saturday with a DS value = 0.77 on Jalan Bandang and a DS value = 0, 93 on North Veterans Road. With a DS value > 0.75, treatment is needed to reduce density or congestion. So the level of service on Jalan Bandang is rated C, while the rating on Jalan Veteran Utara is rated E, so there must be no parking signs installed because it results in a reduction in road capacity.